Analysis of CR, EPS, DER, and PBV on Stock Prices: a Study of The Financial Sector Listed on the Indonesia Stock Exchange in 2019-2023 - Febriya Sista Anggreni; C. Tri Widiastuti; Aditiya Pratama Nugroho (Economic Reviews Journal, 2026)
This study aims to analyze the effect of the liquidity ratio proxied by the Current Ratio (CR), the Profitability ratio proxied by the Earning per Share (EPS), the Solvency ratio proxied by the Debt to Equity Ratio, and the market ratio proxied by Price to Book Value. In financial sector companies listed on the Indonesia Stock Exchange. The research period is five years, namely 2019-2023. The research population includes all financial companies listed on the Indonesia Stock Exchange during the observation period of 2019-2023 totaling 106 companies. The sample selection technique uses a purposive sampling method. Based on the purposive sampling method, 65 financial companies were obtained as research samples. The data analysis method used is Multiple Linear Regression. The results show that the Current Ratio, Earning per Share have a negative and significant effect on stock prices. Debt to Equity Ratio, Price to Book Value have a positive and significant effect on stock prices. The ability of the independent variables, namely Current Ratio, Earnings per Share, Debt to Equity Ratio, and Price to Book Value, to explain the dependent variable, Stock Price, is 0.360 or 36%, while the remaining 64% is influenced by other factors outside the research model.